PRICING IN E-COMMERCE: A SHARIAH PERSPECTIVE - Nurlia, Wa; Saskia, Ani; Maulana, Muhammad Ryan; Ramadhan, Reno (Fakultas Syariah IAIN Kendari, 2025)
This article analyzes pricing in e-commerce from the perspective of sharia economic law, considering the importance of ethics in business practices in the digital era. With the rapid development of technology and the increasing use of e-commerce platforms, buying and selling transactions can now be carried out more quickly and efficiently. However, this convenience also brings challenges, especially related to pricing practices that are often non-transparent and unfair. This study uses a qualitative approach with a descriptive analysis method to explore the views of business actors and consumers regarding the application of sharia principles in pricing. The results of the study indicate that the application of sharia principles, such as transparency, fairness, and the prohibition of usury, is very important to create an ethical and sustainable business environment. By understanding and implementing these principles, business actors can not only increase consumer trust but also contribute to the development of a fairer and more sustainable economic ecosystem.Keywords: Pricing, e-commerce, sharia economic law